Regulation of the Council of Europe: Partial and Enlarged Partial Agreements - M. A. Limonnikova (Московский журнал международного права, 2010)
Partial agreements are not expressly mentioned by the Council of Europe Statute but there are a number of resolutions that contain provisions giving the content of the partial agreement but not its definition. In legal theory this question is treated differently by foreign and Russian scholars. In our view, partial agreement of the Council of Europe is a particular form of cooperation between States within the Council of Europe which operates on the basis of the Committee of Ministers’ resolution in a particular sphere and that concerns only some member States of the Council of Europe. Apart from partial agreements there are enlarged partial agreements (agreements between several Council of Europe member states and non-European countries) and enlarged agreements (agreements between all Council of Europe member states and non-European countries).The Venice Commission of the Council of Europe is an example of partial agreement that has evaluated into an enlarged agreement (the only one in the Council of Europe), where all CoE member-states participate as well as non-European countries such as Brazil, Korea, Kazakhstan, South Africa, Palestinian National Authority and others.